(untitled) (Contemporary Journal of Social Science Review, 2025)
Remittances play a crucial role in the economic stability of South Asian countries, particularly those with a significant workforce employed in the Middle East. While remittance inflows contribute to poverty reduction, improved household welfare, and foreign exchange reserves, they also raise concerns about economic dependency and long-term sustainability. This study examines the dual impact of remittances on South Asian economies, focusing on their benefits and the risks of over-reliance on external income sources. Using a mixed-methods approach, the research integrates quantitative analysis of remittance trends with qualitative insights from policy documents and expert interviews. The findings highlight how remittances influence local Labor markets, investment patterns, and economic diversification efforts. While remittances enhance financial security, they may discourage workforce participation, distort market structures, and create vulnerabilities in national economies. The study underscores the need for policy interventions that transform remittances from a source of short-term financial relief into a driver of sustainable economic growth. Recommendations include promoting productive investments, improving financial literacy, diversifying economic sectors, and strengthening labor protections for migrant workers. The research concludes that while remittances remain a vital economic pillar, South Asian economies must adopt strategic policies to mitigate dependency and foster long-term resilience. This study contributes to academic discussions on migration economics and serves as a valuable resource for policymakers, economists, and development organizations aiming to balance the benefits of remittances with sustainable economic strategies.